Assessment of electrically-driven vehicles in terms of emission impacts and energy requirements: a case study for Istanbul, Turkey - Yagcitekin, Bunyamin; Uzunoglu, Mehmet; Karakas, Arif; Erdinc, Ozan (ELSEVIER SCI LTD, 2015)
Emissions caused by the transportation sector account for a significant portion of the total emissions causing global warming. These emissions must be considered, especially for metropolitan cities with large, numbers of vehicles on roads. Traffic congestion in such metropolitan areas is another reason for the evaluation of different technologies to be utilized in the transportation sector. Istanbul, with a population of approximately 13 million people using approximately 3 million road vehicles, is a suitable example of such metropolitan areas with many traffic problems. Thus, in this study, an assessment of electrically-driven vehicle (EDV) utilization instead of conventional vehicular systems for Istanbul is performed. The possible effects of urban road transportation electrification on carbon dioxide (CO2) emission reduction and the economic benefit in the carbon trade market are investigated. In addition, the possibility of supplying the required vehicle charging energy from renewable sources is also evaluated. Thus, the main contributions of this study are the evaluation of the environmentally friendly operation of EDVs and the investigation of different penetration ratios of EDVs in energy and investment requirements as well as environmental factors. In addition, predictions are provided for the future market of EDVs, accounting for both the use of EDVs and electricity production to obtain highly accurate results. Consequently, a basis for the evaluation of the possible market penetration rate of EDVs is presented. Additionally, the use of sustainable transportation in such metropolitan areas is investigated in this study. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electric vehicle; CO2 emission; Carbon trade market; Energy requirement; Wind energy; POWER; SYSTEM; TRANSPORT; SCENARIOS; HYBRID; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology